Gender and surface effect on rally duration in singles matches at Grand Slam tournaments in 1997-9 and 2007 - Brown, E.; O'Donoghue, P. (World Congress of Performance Analysis of Sport VIII, 2008)
Tournament was found to have a significant effect on the duration of rallies in singles tennis which agrees with previous research studies (Hughes and Clarke, 1995; O`Donoghue and Ingram, 2001; Collison and Hughes, 2003). Coe and Miley (2001) describe many technical, tactical, physiological and psychological differences between tennis match play on different court surfaces that would explain many of the differences found between tournaments in the current investigation. The longer rallies that occur at the French Open result in prolonged matches that induce fatigue increasing error rates and reducing stroke velocity (Vergauwen et al., 1998). Girard and Millet (2004) found that playing on clay courts produced significantly longer rallies, a significantly higher oxygen cost per minute of play and a significantly higher heart rate response then playing on Greenset ® (a fast outdoor surface). The shorter rallies at Wimbledon can be explained by the number of points won through aces and serve winners (Hughes and Clarke, 1995). The tournament effect on service effectiveness may also be attributed to different service placement strategies adopted at different Grand Slam tournaments (Unierzyski and Wieczorek, 2004); players serve wide more often at the French Open and to the middle zone more at Wimbledon. Verlinden et al. (2004) finding that men served more aces and serve winners than women, suggested that men`s greater height and greater ability for force production may explain the shorter rally durations in the men`s game. The differences in tennis performance between the Grand Slam tournaments cannot be attributed entirely to the court surface because different balls are used at the tournaments. The aim of introducing the type 1 at the French Open and type 3 balls at Wimbledon was to reduce the variability in play between the different court surfaces. With the same two players (Roger Federer and Rafael Nadal) contesting the French Open and Wimbledon men`s singles finals in 2006 and 2007, there is evidence of reduced variability between the Grand Slam tournaments. Comparing the results of the current investigation with those of O`Donoghue and Ingram (2001) using the same method allows the effect of the introducing the type 1 and type 3 balls to be examined. The ITF`s decision to formally classify court surface pace and use type 1 balls on the slowest surfaces and type 3 balls on the fastest surfaces has reduced the variability in tennis between the Grand Slam tournaments. In women`s singles, the difference between rally durations at the French Open (9.0s) and Wimbledon (6.1s) in 1997 to 1999 (O`Donoghue and Ingram, 2001) has decreased in 2007 (7.2s and 6.2s respectively). Similarly in men`s singles, the difference between rally durations at the French Open (7.3s) and Wimbledon (3.8s) in 1997 to 1999 has decreased in 2007 (7.6s and 5.4s respectively). Rallies in men`s singles have increased in duration at all four tournaments since 1999 while the duration of rallies in women`s singles has decreased at all tournaments except Wimbledon. This suggests that there have been different developments in men`s and women`s tennis despite the use of the same balls and surfaces in men`s and women`s singles tennis at Grand Slam tournaments. The longer rallies in men`s singles at the French Open could indicate that players are fitter and have better technical ability than in the 1990s. Such improvements allow players to retrieve more balls, prolonging rallies before making errors or not being able to reach a ball played by the opponent. The increased rally lengths at Wimbledon may be explained by the use of the type 3 balls. The slower flight velocity of the type 3 ball gives players more time to play the ball, thus reducing the risk of errors being played and prolonging rally durations. This increased rally duration can increase oxygen cost of play (Smekal et al., 2001). An experiment where players used both type 2 and type 3 balls has shown that rally lengths are significantly longer when type 3 balls are used and that use of the type 3 ball significantly elevated heart rate response of the players (Blackwell et al., 2004). The fact that significant differences still exist between tennis play at the four Grand Slam tournaments has its advantages for the sport. According to Miah (2000), the variation in surface provides excitement in tennis. Furthermore, it can be argued that winning Grand Slam tournaments under varying conditions is a greater achievement than winning Grand Slam tournaments played under consistent conditions. In conclusion, the current investigation has shown that while there is a reduced variability between tennis performance between the four Grand Slam tournaments, there are still significant tournament effects. The most striking result is that rally durations have increased in men`s singles at all 4 tournaments while they have decreased in women`s singles at all of the tournaments except Wimbledon. This has been observed despite men and women using the same balls on the same surfaces. Service is still more important in the men`s game than the women`s game and still more important at Wimbledon than at the other Grand Slam tournaments. The changes between 1997-9 and 2007 indicate that men play longer rallies than before. The serve may have become more important in women`s singles resulting in shorter rallies. The increased rally durations in women`s singles at Wimbledon may result from a change in the speed of the grass surface. These results indicate that the nature of elite tennis has changed over the last 10 years and hence player preparation needs to adapt to the demands of the game today. Follow-up studies using the same computerised system are planned for Grand Slam tournaments in 2017 and 2027.